La «questione del soggetto» come problema pedagogico - Franco Cambi (Firenze University Press, 2009)
During Twentieth-century the western subject has been placed at the centre of scientific dis-cussion. The author shows three way of interpretation: 1) we have to go over traditional vi-sion of western subject; 2) the return of hermeneutic thought about subject; 3) the contempo-rary subjects is managed by new technologies. It's necessary reflects on these questions with increasing attention.